An Initial Approach to Increase Job Satisfaction Through Workplace Spirituality - Bella, Ricardo Luiz Fernandes; Quelhas, Osvaldo Luiz Gonçalves; Ferraz, Fernando Toledo; Barboza, Douglas Vieira; França, Sergio Luiz Braga (Frontiers in Psychology, 2021)
Job satisfaction is a widely discussed topic in work psychology, but what might be the contributions of recent discussions of workplace spirituality? This research allows a qualitative measure of workplace spirituality relevance by workforce perspective that can be reproduced in other organizations through a questionnaire application. The spiritual factors of the workplace were classified according to the Kano model that identifies the potential for actions and investments to be transformed into job satisfaction. In this application, it was identified that investments in the work factors coherence and purpose can generate more than proportional satisfaction in the individuals of this organization. The work factors’ identity, values, cohesion, meaning and climate could generate a proportional satisfaction to the investments. The inner life and community factors cannot generate satisfaction, but when investments levels in these factors did not meet the expectations, it potentially generates dissatisfaction. Finally, investments in belonging, connection and environment factors were indifferent to the satisfaction level in this organization. The researchers also pointed out investments’ opportunities to the organization.